Creativity Regime and Internship Practices on MBKM Policy - Salim, Permata Mohamad (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. The internship practice has become a regularity in responding to the interconnectedness of the labor market and education system in Indonesia. The Certified Internship and Independent Study Program (MSIB) is part of MBKM policies initiated by the Ministry of Education and Culture. It represents the state's position to capitalize on creativity discourse while continuing the connection between higher education and industry. Based on the literature review, this qualitative research provides an overview of the widespread phenomenon of internships. This research aims to explore the capacity of the creativity regime to exert hegemony through the MBKM policy that encourages internship practices. On one hand, internship programs play a role in making the educational ecosystem more open to new labor market challenges. However, students believe that without internships, their chances of finding employment after graduation are reduced. As a result, through the mechanisms of regulation and the activation of discourse within the creative regime, students have prioritized internships as spaces for exploring subjective experiences in realizing their authentic, engaging, and unique selves. By reflecting the characteristics of contemporary society as described by Andreas Reckwitz, which is a singularized society. Keywords: Creativity Regime, Singularization, Internship, MBKM Program, MSIB, Reckwitz. Abstrak. Praktik magang telah menjadi regularitas baru dalam merespons keterkaitan antara pasar tenaga kerja dan sistem pendidikan di Indonesia. Program Magang Bersertifikat dan Studi Independen (MSIB) merupakan bagian dari Kebijakan Merdeka Belajar Kampus Merdeka (MBKM) yang diinisiasi oleh Kementerian Pendidikan dan Kebudayaan. Program ini mencerminkan posisi negara dalam memanfaatkan wacana kreativitas bersamaan dengan logika link and match antara pendidikan tinggi dan industri. Menggunakan studi literatur, penelitian kualitatif ini memberikan gambaran tentang fenomena magang yang tersebar luas. Penelitian ini bertujuan mengeksplorasi kapasitas rezim kreativitas dalam menciptakan hegemoni melalui kebijakan MBKM yang mendorong praktik magang. Di satu sisi, program magang berperan dalam membuka ekosistem pendidikan terhadap tantangan pasar tenaga kerja yang baru. Pada sisi lainnya, mahasiswa percaya bahwa tanpa magang peluang mereka untuk mendapatkan pekerjaan setelah lulus berkurang. Hasil dalam penelitian ini menunjukan melalui mekanisme regulasi dan aktivasi wacana dalam rezim kreativitas, mahasiswa telah memprioritaskan magang sebagai ruang eksplorasi pengalaman subjektif untuk mewujudkan diri mereka yang otentik, menarik, dan unik. Merefleksikan karakteristik masyarakat kontemporer sebagaimana yang dijelaskan oleh Andreas Reckwitz, yaitu masyarakat yang tersingularisasi. Kata Kunci: Rezim Kreativitas, Singularisasi, Magang, Program MBKM, MSIB, Reckwitz.